The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3174/ajnr.a3649
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cerebral Arterial Spin-Labeled Perfusion in Children with Neurofibromatosis Type 1

Abstract: BACKGROUND AND PURPOSE:Neurofibromatosis type 1 is associated with increased risk for stroke, cerebral vasculopathy, and neurocognitive deficits, but underlying hemodynamic changes in asymptomatic children remain poorly understood. We hypothesized that children with neurofibromatosis type 1 have decreased cerebral blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…). Yeom et al have shown decreased CBF in a cohort of NF1 patients without steno‐occlusion or Moyamoya disease, particularly in the posterior circulation and borderzones, which they propose might be due to vasculopathy in cerebral microvasculature or alteration in cerebral metabolic demand (Fig. ).…”
Section: Disorders Of Decreased Cbfmentioning
confidence: 99%
“…). Yeom et al have shown decreased CBF in a cohort of NF1 patients without steno‐occlusion or Moyamoya disease, particularly in the posterior circulation and borderzones, which they propose might be due to vasculopathy in cerebral microvasculature or alteration in cerebral metabolic demand (Fig. ).…”
Section: Disorders Of Decreased Cbfmentioning
confidence: 99%
“…Recent diffusion tensor imaging (DTI) study in human NF1 [ 11 ] demonstrated increased apparent diffusion coefficient (ADC) values localised in the caudate and other deep grey nuclei, diencephalon and frontal white matter in NF1 children compared to controls, consistent with decreased neuronal density or myelin sheath disorganisation; the extent of these effects was associated with neurological symptoms. Other imaging studies in human NF1 have identified reduced cortical GABA [ 12 , 13 ], reduced cerebral perfusion [ 14 ], alteration in diffusion-weighted imaging [ 15 ] and abnormal network connectivity on resting state fMRI [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…While volumetric and diffusion analysis can be used to probe macro-and microstructural changes, respectively, arterial spinlabeling (ASL) cerebral blood flow is increasingly used clinically to obtain advanced physiologic information. [15][16][17][18] ASL may be particularly useful in the pediatric population because it does not require intravenous contrast or ionizing radiation. However, only a few studies have examined ASL CBF changes in children.…”
mentioning
confidence: 99%